APAKAH INDEPENDENSI AUDIT DAN PEMAHAMAN GOOD GOVERNANCE MEMPENGARUHI KINERJA AUDITOR DENGAN TIME BUDGET PRESSURE SEBAGAI VARIABLE MODERASI? - Islana Andalucia Hartoyo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This analysis was made to determine the effect of Independence, Understanding of Good Governance on Auditor Performance with Time Budget Pressure as a moderating variable. The population in this study are auditors who work in Public Accountant Firms in DKI Jakarta. From the distribution questionnaires, obtained 50 respondents who filled out the questionnaire given through Google Form. The results concluded that Understanding of Good Governance has a significant positive effect on Auditor Performance. While Independence has no effects on Auditor Performance. And this study shows that Time Budget Pressure does not weaken the influence of Independence nor Understanding of Good Governance on Auditor Performance. For future research to not only provide questionnaires, but also conduct interviews with respondents to get a higher quality of answers, and also adds other variables that can provide more accurate and reliable answers.